2019
DOI: 10.1590/s1984-29612019008
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular insights of a new species of trypanorhynchid cestode parasite, Nybelinia exostigmi, in the Narrowstripe cardinal fish Apogon exostigma

Abstract: Forty specimens of the Narrowstripe cardinal fish Apogon exostigma were examined for gastrointestinal helminthes, and 62.5% were infected with a new trypanorhynchid larval cestode parasite. The morphology of its larval stage was studied based on light and scanning electron microscopy. The data revealed plerocercoid larvae characterized by a pyriform body lined with prominent microtriches; the acraspedote scolex had four overlapping bothridia; four tentacles protruded through the pars bothridialis; the armature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Further, the presence of larvae in the fish musculature may release toxins that affect humans (Deadorff et al, 1984;Caira and Jensen, 2017). Previous reports have concluded that experimental inoculation of Trypanorhyncha species extracts is responsible for immune responses in mice, indicating the possibility of allergic reactions in humans (Vásquez-López et al, 2001;Gòmez-Morales et al, 2008;Al Quraishy et al, 2019). Despite the worldwide distribution of these parasites in commercial fishes, and the great diversity of their species, trypanorhynchids are still a relatively poorly studied group Menezes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the presence of larvae in the fish musculature may release toxins that affect humans (Deadorff et al, 1984;Caira and Jensen, 2017). Previous reports have concluded that experimental inoculation of Trypanorhyncha species extracts is responsible for immune responses in mice, indicating the possibility of allergic reactions in humans (Vásquez-López et al, 2001;Gòmez-Morales et al, 2008;Al Quraishy et al, 2019). Despite the worldwide distribution of these parasites in commercial fishes, and the great diversity of their species, trypanorhynchids are still a relatively poorly studied group Menezes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%